The theory of symbols of purity-analysis of symbols in Me-nyimah Kuala Ritual of the Kedayan community in Kampung Kuala Nyalau, Bintulu, Sarawak - Mohamad Adnan, Mohamad Syukri; Magiman, Mohamad Maulana; Bokhari, Semsolbahri; Mohammad Ramli, Mohammad Saufi (Assoc Advancement Zoology, 2023)
Menyimah Kuala (Feeding the Confluence) is one of the ceremonies still performed by the Kedayan community in Kampung Kuala Nyalau, Bintulu, Sarawak to express their gratitude to God and the supernatural powers for the sustenance enjoyed, to avoid any disasters and unto-ward incidents to the local community, and as a closing to the Makan Tahun (Annual Feast) ritu-al. Based on this study, there are no findings from previous researchers about the performance of the Menyimah Kuala ritual. In fact, according to the villagers, the ritual is only performed by the Kedayan community living in Nyalau, Bintulu. The focus of this paper is to uncover the ritual’s process and to analyse symbols found in the ritual using the Theory of Symbols of Pu-rity (2020). This study uses the qualitative method (ethnography) which includes Field Study, Participant Observation, Interview, and Library Review. Based on the study, it was found that the ritual performed to attain well-being from either God or supernatural powers are based on the concept of purity which coincides with the Theory of Symbols of Purity (2020) introduced by Mohamad Maulana.